Innovation through Knowledge Transfer 2012 - Howlett, Robert J.; Gabrys, Bogdan.; Musial-Gabrys, Katarzyna.; Roach, Jim. (Smart Innovation, Systems and Technologies, 2013)
Across the world there is growing awareness of the importance of innovation and knowledge transfer. Innovation in the sense of generating new knowledge and making better use of existing knowledge, coupled with knowledge transfer and sharing paradigms, have never been more relevant to the universities, industry, commerce and the third sector. This volume represents the proceedings of the Innovation through Knowledge Transfer 2012 Conference which formed an excellent opportunity to disseminate, share and discuss the impact of innovation, knowledge sharing, enterprise and entrepreneurship. The volume contains papers presented at a Workshop on The Meta Transfer of Knowledge: Challenges in the Transfer of Knowledge in Industry, others from thematic sessions on Next-Practice in University Based Open Innovation, Social Innovation and Related Paradigms, Engagement with Industry and Commerce and Knowledge Exchange. All papers were thoroughly reviewed by referees knowledgeable in practical and theoretical aspects of the subject.